Apakah Variabel Makroekonomi Berpengaruh terhadap Indeks Harga Saham di Asia Tenggara? - Hana Tamara Putri (Universitas Batanghari Jambi, 2023)
The possession of shares indicates a level of investment in or ownership of a corporation. The value of the company's stock is affected by a number of macro and micro variables. Given these conditions, the purpose of this research is to determine the impact of global gold and crude oil prices, interest and inflation rates, and currency rates on the South East Asia (Case study: Indonesia, Malaysia, and Thailand) composite stock price index from 2010 to 2020. Secondary information gleaned from the internet is analyzed quantitatively for this research. This study makes use of the classical assumption test, the hypothesis test, and the coefficient of determination to analyze the data. This research looked at data from Indonesia and Malaysia between 2010 and 2020. This study looks at the potential influences on Indonesia's and Malaysia's joint stock price index of global gold prices, crude oil prices, interest rates, inflation, and currency rates. T test results show a statistically significant relationship between the independent variables and the composite stock price index, while f test results show that the independent variables individually do not have a statistically significant relationship with the dependent variable. include the cost of gold and crude oil across the globe. The dependent variable as a whole does not have a statistically significant impact on the Kuala Lumpur composite index, according to the test findings in Malaysia, which are f = fcount f table (1.524 5.05). According to the t test, however, the Kuala Lumpur Composite Index is affected by a number of different factors in Malaysia. In contrast, for the Kuala Lumpur composite index, f = fcount f table (0,910 5.05) indicates that the dependent variable as a whole has no statistically significant impact. Based on the t-test's findings, the Stock Exchange of Thailand is not significantly impacted by any one independent variable in Malaysia. There is a positive correlation between the JCI and the global price of gold and crude oil in Indonesia, whereas there is a negative correlation between the JCI and interest rates, inflation, and the currency rate. In the meanwhile, the KLCI in Malaysia is negatively impacted by a number of global factors, including the price of gold, the price of crude oil, interest rates, inflation, and currency rates. Meanwhile, in Thailand, the SET is negatively impacted by a variety of external factors, including global gold prices, global crude oil prices, interest rates, inflation, and currency exchange rates.